TINGKAT PENGETAHUAN DAN PENDIDIKAN IBU HAMIL TENTANG KEPATUHAN MENGKONSUMSI TABLET TAMBAH DARAH (FE) DI PUSKESMAS KASSI-KASSI KOTA MAKASSAR - Wirawati Amin,; Afriani, Afriani; Indriani, Indriani; Fitriana, Fitriana (Jurnal Cakrawala Ilmiah, 2023)
Anemia is an indirect cause of maternal mortality, which can increase the risk of complications in the form of bleeding. Therefore, the Ministry of Health recommends that pregnant women consume at least 90 iron pills during pregnancy. However, it is influenced by the compliance of pregnant women consuming Fe tablets. This study aims to determine the relationship between education and knowledge level of pregnant women with adherence in consuming Fe tablets. The results of this study are expected to be input and useful for pregnant women about Fe tablets. The type of research used is Analytical Survey with Cross Sectional Study approach. Sampling using technique of Consecutive Sampling counted 78 respondents by using questioner. The result of bivariate analysis of education level with compliance of Fe tablet tablet showed that p value (0.001) < α (0,05) and result of bivariate analysis of knowledge with compliance consuming Fe tablet showed that p value (0,026) < α (0,05). So it is concluded that there is a significant relationship between the education level of pregnant women with compliance of Fe tablets and there is a significant relationship between the knowledge of pregnant women with compliance of Fe tablets. Therefore, it is suggested to increase the insight about penitngnya Fe tablet so that mother can know the benefits and consequences that will occur if not consuming Fe tablet for the fetus and also pregnant mother herself.